(untitled) (Research, Society and Development, 2022)
The objective was to evaluate four forage cultivars, Basilisk, Marandu, Paiaguás and Zuri submitted to four plaster doses: 0, 5, 10 and 15 Mg ha-1. The experiment was carried out in pots and conducted on a bench in full sun. DIC and 4x4 factorial scheme were used. The production of green and dry mass of the aerial part was evaluated in each cut and total, leaf/stem ratio in green and dry matter, number of tillers, leaf expansion rate, production of green and dry root mass in layers of 0.1m and total, number of tillers, leaf nitrogen and C/N ratio. The cultivar Paiaguás producers the most dry mass, Basilisk has the best leaf/stem ratio and the highest number of tillers, the cultivars Paiaguás and Marandu have the highest rate of leaf expansion. There was interaction for leaf/stem ratio in the dry mass. The cultivar Zuri produces a larger amount of root, in the 0.1 a 0.2m layer there was no difference between levels. the application of plaster provided root increase in the layer from 0.3 to 0.4m in depth. The cultivar Marandu has the highest N content and the lowest C/N ratio. The nitrogen content increases and the C/N ratio decreases, both linearly with plaster doses.